Risk Management Practices to Strengthen Public Sector Accountability - Abdul Rasid, Siti Zaleha; Abu Bakar, Bebe; Mohd Rizal, Adriana; Baskaran, Shathees (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aims: Risks can challenge the public sector’s service delivery system and growth sustainability. While the notion of modern accountability demands some display of risk management (RM) initiatives, less attention has been given to the impact of RM practices on organisational accountability as well as the effect of performance measurement system (PMS) use on RM practices. Drawing from the resource-based view, this study attempts to investigate the predictive effect of RM practices and (PMS) use on accountability by using a mediation framework. Design/Methodology/Approach: Cross-sectional survey is applied to collect data from the top management of the Malaysian Federal Statutory Bodies (FSBs). The research framework is tested by analysing the data of 110 Malaysian FSBs through the structural equation modelling technique (PLS-SEM). Research findings: The result of the study demonstrates that PMS use for monitoring and PMS use for attention-focusing have a significant positive effect on RM practices. Additionally, RM practices mediate the relationship between PMS use and accountability. Theoretical contribution/Originality: This paper is among the few to assess the effect of PMS use on RM practices and to determine the mediation effect of RM practices on the relationship between PMS use and accountability. Practitioner/Policy implication: These findings provide valuable insights for authorities in the public sector on the ways to enhance public sector governance through new mechanisms of accountability such as RM practices. Research limitation/Implication: This study uses a non-probability sampling. Considering the difference in design and use of control systems among the different sectors or industries, the results may not be generalised to other populations. However, the outcome of this study suggests that RM practices do strengthen public sector accountability with the appropriate use of the PMS. Keywords: Risk Management, Performance Measurement System, Accountability, Public Sector JEL Classification: M41